2022
DOI: 10.2169/internalmedicine.8205-21
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with <i>Pneumocystis jirovecii</i> Pneumonia in Patients with Rheumatoid Arthritis Receiving Methotrexate: A Single-center Retrospective Study

Abstract: Objective To investigate the risk factors for the development of Pneumocystis jirovecii pneumonia (PCP) in patients with rheumatoid arthritis (RA) undergoing methotrexate (MTX) therapy. Method This single-center retrospective cohort study included consecutive patients with RA who received MTX for at least one year. The study population was divided into PCP and non-PCP groups, depending on the development of PCP, and their characteristics were compared. We excluded patients who received biologic disease-modifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…Another study at high RoB found a similar risk of TB with abatacept compared with other b/tsDMARDs 74. The risk of pneumonia due to Pneumocystis jirovecii was increased with methotrexate combined with other csDMARDs, compared with methotrexate alone (aHR: 5.98 (95% CI 1.91 to 18.74)) (one study at high Rob) 34. Hospitalisation due to infection by SARS-CoV-2 was more likely with non-TNFi (analysed together) compared with csDMARDs and TNFi in one study,27 and with rituximab compared with TNFi in another (both at high RoB) 28.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Another study at high RoB found a similar risk of TB with abatacept compared with other b/tsDMARDs 74. The risk of pneumonia due to Pneumocystis jirovecii was increased with methotrexate combined with other csDMARDs, compared with methotrexate alone (aHR: 5.98 (95% CI 1.91 to 18.74)) (one study at high Rob) 34. Hospitalisation due to infection by SARS-CoV-2 was more likely with non-TNFi (analysed together) compared with csDMARDs and TNFi in one study,27 and with rituximab compared with TNFi in another (both at high RoB) 28.…”
Section: Resultsmentioning
confidence: 97%
“…From a total of 2961 references (after de-duplication), 226 were selected for a full-text review and 59 observational studies fulfilled the inclusion criteria 16–74. In addition, 2 RCTs with a primary safety outcome,2 3 and 28 RCTs/LTEs from the efficacy SLR,75–102 were included (flow chart in online supplemental figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S. I. Ohmura и соавт. [46] исследовали факторы риска развития ППн у 334 пациентов с РА, получающих МТ в качестве монотерапии или комбинации с другими БПВП не менее 1 года, в рамках моноцентрового ретроспективного когортного исследования. Ни один пациент не получал профилактическую терапию.…”
Section: группы рз «невысокого» рискаunclassified